Theoretical Writings : Alain Badiou. - Badiou, Alain (Athlone contemporary European thinkers., 2004)
Alain Badiou is arguably the most important and original philosopher working in France today. Swimming against the tide of postmodern orthodoxy, Badiou's work revitalizes philosophy's perennial attempt to provide a systematic theory of truth. This volume presents for the first time in English a comprehensive overview of Badiou's ambitious system. Beginning with Badiou's controversial assertion that ontology is mathematics, this volume sets out his theory of the emergence of truths from the singular relationship between a subject and an event. Also included is a substantial extract from Badiou's.